Wanita G2P1A0 Hamil 39 Minggu Belum Inpartu dengan Eklampsi Janin Tunggal Hidup dan Suspek Pertumbuhan Janin Terhambat - Karina Azlia Amanda; Karunia Santi; Ratna Dewi Puspitasari (CV. Jasa Sukses Abadi, 2022)
Eclampsia is a syndrome characterized by hypertension and proteinuria after 20 weeks of gestation and can be accompanied by organ damage and seizures. Preeclampsia and eclampsia are the causes of 30-40% of perinatal deaths and are one of the obstetric complications that cause a lot of morbidity and mortality in addition to bleeding and infection. The female patient, 21 years old, was taken to Abdul Moeloek Hospital by her family at the referral of Bumi Waras Hospital with complaints of pregnancy with high blood pressure and a history of seizures before hospital admission. From the examination of an obgyn specialist outside, an ultrasound was performed with the results of intauterine growth restriction. The gestosis index in this patient is 10. The diagnosis in this patient Gravida 2 Partus 1 Abortion 0 (G2P1A0) 39 weeks pregnant and not yet parturition with eclampsia of a live singleton fetus with cephalic presentation and suspect IUGR (intrauterine groth restriction). The patient received active management after receiving medical and observative therapy. Medical therapy consists of MgSO4, nifedipine and dexamethasone. The diagnosis and management in this case have been adjusted according to the reference.